Authoritative and Class-Sensitive Parents: Parental Identities Shaped through Personal and Political Transitions - Mendel, Maria (International Journal about Parents in Education, 2023)
Memories that support our identity usually appear in narratives that we produce. This article presents research findings based on the analysis of biographical narratives of parents involved in the project entitled Parents, school and educational transition in Poland: 1989–2009 (University of Gdansk, 2006–2009). The parents told stories about their childhood (and school education in the former system) and about their parenthood by which they experienced the new social order (and their children’s school education). Being interested in identity work in the light of memory processes, the author analysed parts of interviews that reflect a specific type of influential memory. It resulted in a descriptive reconstruction of the parental identity, strongly informed by the parents’ recollections of their own school experience. On the one hand, memories seem to shape parents’ approaches to the teaching staff and the school. On the other hand, they show what parents learned throughout their transition from childhood to parenthood. Some aspects of identity remain the same, regardless of changing social and political contexts and regardless of personal educational transition. Still, parental identity, based solidly in the past, may determine the future of school education, particularly in terms of family – school partnerships.